Coronavirus (COVID-19) Impacts on Malaysian Fisheries Sectors: Lesson Learned from the Movement Control Order (MCO) - Ameer Farhan Mohd Arzaman; Hayatul Safrah Salleh; Abdul Mutalib Embong; Kais Amir Kadhim; Norzamziah Afzainizam; Loi Hoang Huy Phuoc Pham; Nurul Ashikin Abdul-Kadir; Nur Yuhanis Mohd Nasir (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research